Outcome of Probing for Congenital Naso-Lacrimal Duct Obstruction - Sharife, Mozammel Hoq; Uddin, M Jalal; Ahmed, Mostak (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Objective: The study was conducted to evaluate outcome of probing for congenital nasolacrimal duct obstruction. It was an interventional study at a tertiary level hospital of Chittagong. Methods: The study was conducted during April 2009 to March 2013 (04 years). Total 120 eyes of 102 children of 1-3 years age group were probed. Minimum follow up time was 01 year. Results: 110 eyes fully cured, 05 eyes needed re-probing, 03 eyes needed Dacrocystorhinostomy operation (DCR) and 02 cases were dropped out. Male female ratio was 72 (60%) and 48 (40%). Conclusion: Outcome of probing is better among 1-2 years age group than that of 2- 3 years age group. A discussion is made with updated literature review. DOI: http://dx.doi.org/10.3329/cmoshmcj.v14i1.22879 Chatt Maa Shi Hosp Med Coll J; Vol.14 (1); Jan 2015; Page 36-37